2006
DOI: 10.1021/np060361d
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Putative Bryostatin Polyketide Synthase Gene Cluster from “Candidatus Endobugula sertula”, the Uncultivated Microbial Symbiont of the Marine Bryozoan Bugula neritina

Abstract: The bryostatins are protein kinase C modulators with unique structural features and potential anticancer and neurological activities. These complex polyketides were isolated from the marine bryozoan Bugula neritina, but recent studies indicate that they are produced by the uncultured symbiotic bacterium "Candidatus Endobugula sertula" ("E. sertula"). Here we present the putative biosynthetic genes: five modular polyketide synthase (PKS) genes, a discrete acyltransferase, a beta-ketosynthase, a hydroxy-methyl-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
263
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 301 publications
(274 citation statements)
references
References 52 publications
3
263
0
8
Order By: Relevance
“…Some polyketides produced by trans-AT PKSs, such as pederin (21,22,43), bryostatin (45,46), and rhizoxin (12,47), are known to participate in host defense and pathogenicity in symbiotic associations. It has also been suggested that PKS-NRPS compounds such as the microcystins, sometimes produced by cyanobacterial symbionts, may contribute to the chemical defense of lichens against grazers (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Some polyketides produced by trans-AT PKSs, such as pederin (21,22,43), bryostatin (45,46), and rhizoxin (12,47), are known to participate in host defense and pathogenicity in symbiotic associations. It has also been suggested that PKS-NRPS compounds such as the microcystins, sometimes produced by cyanobacterial symbionts, may contribute to the chemical defense of lichens against grazers (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have provided convincing evidence that a number of secondary metabolites originally ascribed to sponges, bryozoans, and other macroorganisms are of microbial biosynthetic origin (44)(45)(46). Further, microbial metabolites such as 2,3-indolinedione from a bacterium associated with crustacean embryos have been shown to defend hosts against pathogen infection (47).…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic treatments, which reduced 'E. sertula' density in B. neritina adult colonies, decreased bryostatin concentration in B. neritina, and lowered expression of bryA, a portion of the bryostatin biosynthetic gene cluster (Davidson et al, 2001;Hildebrand et al, 2004;Sudek et al, 2007). Such antibiotic treatments of B. neritina did not alter the growth, settlement or metamorphosis of B. neritina (Davidson et al, 2001;Lopanik et al, 2004), but the reduction of bryostatins did increase the palatability of the larvae to fish (Lopanik et al, 2004).…”
Section: Introductionmentioning
confidence: 99%